Enhancement of power in the concentric phase of the squat and jump: Between-athlete differences and sport-specific patterns - Zemková, E.; Vilman, T.; Cepková, A.; Uvacek, M.; Olej, P.; Simonek, J. (Journal of Human Sport & Exercise, 2017)
This study compares the differences in peak and mean power in the acceleration, as well as over the entire concentric phase of jumps and squats performed with and without countermovement (i.e. delta power) in athletes of different specializations. The participants performed either barbell squats or barbell jumps with and without countermovement bearing a weight of 70% 1RM. Results identified a significantly higher delta mean power in the entire concentric phase of jumps than in squats for high jumpers (29.8%, p=0.009) and volleyball players (24.3%, p=0.027). More specifically, their values were significantly higher during jumps in indoor volleyball players but not in beach volleyball players. On the other hand, rock & roll performers exhibited a significantly higher delta mean power during squats than jumps (19.5%, p=0.034) but this was only evident in those who specialized in acrobatics as opposed to dance. However, the values did not differ significantly during either jumps or squats for hockey players (9.5%, p=0.424) and karate competitors (11.6%, p=0.331). A similar trend was observed for peak and mean power in the acceleration phase of jumps and squats. It may be concluded then, that enhancement of power in the concentric phase of jumps and squats bearing an external load, differs in athletes with diverse demands on the explosive strength of their lower limbs. For most athletes, jumping may be considered a more specific alternative for the estimation of the ability to utilize elastic energy during countermovement exercise, whereas for others it may be the squat.